2018
DOI: 10.1111/den.13255
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis with hemostatic forceps for bleeding during endoscopic necrosectomy

Abstract: https://onlinelibrary.wiley.com/page/journal/14431661/den13255-sup-0001-vids1.htm a video of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Only two studies have reported on the use of Coagrasper for arterial bleeding during EN [8,9]. These reports documented successful hemostasis for small-vessel bleeding within the gastric wall or the WON cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have reported on the use of Coagrasper for arterial bleeding during EN [8,9]. These reports documented successful hemostasis for small-vessel bleeding within the gastric wall or the WON cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, an active bleeding gastric ulcer was detected at the greater curvature of the gastric body. Successful endoscopic hemostasis using hemostatic forceps (RAICHO2, Kaneda Medix, Osaka, Japan) was achieved by an operating endoscope (GIF‐Q260J, Olympus) with hood attachment (D‐201‐11804, Olympus) 4 . Blind tube insertion can potentially injure the gastrointestinal tract 5 .…”
Section: Brief Explanationmentioning
confidence: 99%
“…Successful endoscopic hemostasis using hemostatic forceps (RAICHO2, Kaneda Medix, Osaka, Japan) was achieved by an operating endoscope (GIF-Q260J, Olympus) with hood attachment (D-201-11804, Olympus). 4 Blind tube insertion can potentially injure the gastrointestinal tract. 5 Using both an ultra-thin endoscope and an endoscopic guide tube, a thick suction tube could be inserted and placed appropriately in the stomach.…”
mentioning
confidence: 99%